The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1055/a-1065-1786
|View full text |Cite|
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in Thyroid Hormone Transporter Genes MCT8, MCT10 and Deiodinase DIO2 Contribute to Inter-Individual Variance of Executive Functions and Personality Traits

Abstract: Thyroid hormones are modulators of cognitive functions, and changes in hormone levels affect intelligence, memory, attention and executive function. Single nucleotide polymorphisms (SNPs) of transporter proteins MCT8, MCT10 and deiodinase 2 (DIO2) influence thyroid metabolism and could therefore contribute to inter-individual variance of cognitive functions. This study investigates the influence of these SNPs using an extensive neuropsychological test battery. 656 healthy participants aged 18–39 years were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…This negative psychology can directly or indirectly affect the smooth operation of the procedure and postoperative recovery. However, to date, relevant studies have mainly focused on the impact of negative emotions, such as anxiety and depression, on TNs (17)(18)(19)(20)(21). The results herein revealed that patients with TNs undergoing MWA had depression and anxiety at different times, and some even experienced both emotions simultaneously.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This negative psychology can directly or indirectly affect the smooth operation of the procedure and postoperative recovery. However, to date, relevant studies have mainly focused on the impact of negative emotions, such as anxiety and depression, on TNs (17)(18)(19)(20)(21). The results herein revealed that patients with TNs undergoing MWA had depression and anxiety at different times, and some even experienced both emotions simultaneously.…”
Section: Discussionmentioning
confidence: 73%
“…Such negative emotions can directly or indirectly affect the smooth operation and postoperative recovery. To date, studies have mainly focused on the impact of negative emotions, such as anxiety and depression, on TNs (17)(18)(19)(20)(21); with little attention on the impact of anxiety and depression on the prognosis of patients with TNs. Therefore, this current study explored the risk factors of a…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the HPT axis dysfunction can cause emotional and psychotic symptoms, possibly due to thyroid hormone interference with metabolic processes and intracellular signaling pathways ( Glombik et al, 2021 ). On the other hand, abnormal thyroid hormone levels are known to negatively affect cognitive function ( Uter et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The subjects carrying the DIO2-Thr92Ala polymorphism had consistently lower femoral neck and total hip densities than wild-type subjects, accompanied by significantly higher levels of bone turner markers, which indicated a role for the DIO2 gene in the regulation of bone formation [ 8 ]. Recent research has also shown that single nucleotide polymorphisms (SNPs) of DIO2 influence thyroid metabolism, resulting in neurological disease [ 9 ]. Thyroid hormones (THs) have pivotal roles in the development and growth of the craniofacial skeleton, and their action in target tissues is dependent on the intracellular concentration of T3, which is locally regulated by DIO2 and deiodinase 3 ( DIO3 ) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%